APPLICATION OF PFC 3D FOR SLOPE MOVEMENT ON COLLUVIAL SOIL - Nguyen Dinh Tu; Kenji Aoki (Geological Engineering Department Universitas Gadjah Mada, 2015)
In the mountainous area of the tropics, soil creep often occurs on residual soil and colluvial deposit. The rate of this phenomenon varies from very slow to extremely slow and is difficult to detect without equipment as well as model. Within PFC3D (Particle Flow Code in three dimensions) granular materials such as soils are simulated by balls. And the PFC3D model was applied for colluvial soil creep. Although existing of some limitations, this application determined direction of creeping as well as zone of creeping of culluvial soil.